Disputed Rulership in Upper Egypt: Reconsidering the Second Stela of Kamose (K2) - Flammini, Roxana Claudia (2013)
The Second Stela of Kamose (K2) has received a wide spectrum of analyses from different points of view. This paper presents a discussion on the use of the title hq3 and on the conception of the social bonds sustained by the Hyksos ruler as preserved in the text.